2015
DOI: 10.1371/journal.pone.0141946
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxypropyl-β-Cyclodextrin Acts as a Novel Anticancer Agent

Abstract: 2-Hydroxypropyl-β-cyclodextrin (HP-β-CyD) is a cyclic oligosaccharide that is widely used as an enabling excipient in pharmaceutical formulations, but also as a cholesterol modifier. HP-β-CyD has recently been approved for the treatment of Niemann-Pick Type C disease, a lysosomal lipid storage disorder, and is used in clinical practice. Since cholesterol accumulation and/or dysregulated cholesterol metabolism has been described in various malignancies, including leukemia, we hypothesized that HP-β-CyD itself m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 71 publications
2
54
0
3
Order By: Relevance
“…13) We also demonstrated that 2-hydroxypropyl-β-CyD (HP-β-CyD) inhibits leukemic cell proliferation at physiologically available doses without significant adverse effects. 14) More recently, we prepared tumor targeting ligand-appended M-β-CyD, namely folate-appended M-β-CyD (FA-M-β-CyD), to achieve tumor-selective antitumor activity. 15) FA-M-β-CyD induced strong antitumor activity beyond M-β-CyD and doxorubicin without significant adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…13) We also demonstrated that 2-hydroxypropyl-β-CyD (HP-β-CyD) inhibits leukemic cell proliferation at physiologically available doses without significant adverse effects. 14) More recently, we prepared tumor targeting ligand-appended M-β-CyD, namely folate-appended M-β-CyD (FA-M-β-CyD), to achieve tumor-selective antitumor activity. 15) FA-M-β-CyD induced strong antitumor activity beyond M-β-CyD and doxorubicin without significant adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various bioactivities of CyDs have been demonstrated, and CyDs have been used as active pharmaceutical ingredients (APIs) against Niemann-Pick disease type C (NPC), [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] leukemia, 77) hyperlipidemia, 78) Alzheimer's disease, [79][80][81][82][83][84] cerebral ischemic injury, 85) atherosclerosis, 86) diabetic kidney disease, 87) chronic renal failure, 88) AIDS, 89,90) influenza, 91) peripheral artery disease, 92) sterility, [93][94][95] solid cancers, [96][97][98][99][100][101] bacterial growth, 102) α-synucleinopathy, 103) GM1-gangliosidosis, 104) septic shock, [105][106][107] hypervitaminosis, 108) and transthyretin-related familial amyloidotic polyneuropathy (FAP) …”
Section: Cyclodextrin-based Supramolecular Pharmacology and Drug Discmentioning
confidence: 99%
“…As a result, CyDs may possess potential as API for GM1-gangliosidosis. 65) demonstrated that HP-β-CyD itself has anticancer effects against various leukemic cell lines derived from acute myeloid leukemia (AML), acute lymphoblastic leukemia and chronic myeloid leukemia (CML). HP-β-CyD decreased cholesterol level in the cells, and lead to obvious G2/M cell-cycle arrest and apoptosis.…”
Section: Hp-β-cyd For Treatment Of Niemann-pick Disease Type C (Npc)mentioning
confidence: 99%